Pendekatan Integratif dalam Manajemen Dengue - Raymond R. Tjandrawinata (MEDICINUS, 2025)
Dengue, as one of the most challenging tropical diseases of the 21st century, continues to present significant clinical and epidemiological complexities in developing countries, including Indonesia. With the increasing incidence of global dengue infections and the limited availability of definitive therapeutic options, clinical management is shifting toward optimizing supportive therapy and exploring adjuvant strategies to improve key clinical parameters such as hemodynamic and platelet count. By emphasizing the role of two interventions, Gelafusal (gelatin solutions) as a colloid fluid for resuscitation and Psidii (Psidium guajava folium extracts) as a platelet production-stimulating agent, through the lens of bioethics, pharmacodynamics, and evidence-based clinical strategies, this review offers a critical reflection on the opportunities and limitations of applying multimodal interventions in dengue management.